2016
DOI: 10.1007/978-3-319-46379-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Exact Learning of Juntas from Membership Queries

Abstract: In this paper we study adaptive and non-adaptive exact learning of Juntas from membership queries. We use new techniques to find new bounds, narrow some of the gaps between the lower bounds and upper bounds and find new deterministic and randomized algorithms with small query and time complexities.Some of the bounds are tight in the sense that finding better ones either gives a breakthrough result in some long-standing combinatorial open problem or needs a new technique that is beyond the existing ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Therefore the class d-Junta is almost optimally learnable. Bshouty and Costa, [49], close the above gap and showed that…”
Section: D-xor: Sincementioning
confidence: 80%
See 3 more Smart Citations
“…Therefore the class d-Junta is almost optimally learnable. Bshouty and Costa, [49], close the above gap and showed that…”
Section: D-xor: Sincementioning
confidence: 80%
“…A better query complexity can be obtained from the reduction in [49]. See the following Table . The outputs of the above algorithms are the Fourier representation of the decision tree and, therefore, they are non-proper learning algorithms.…”
Section: By Lemma 14 We Getmentioning
confidence: 99%
See 2 more Smart Citations
“…Learning from membership queries, [1], has fueled the interest of many papers due to its diverse applications in various areas including group testing [2], pooling design for DNA sequencing [3], blood testing [4], functional genomics (molecular biology) [5], chemical reactions [6,7], multi-access channel communications [2,8], whole-genome shotgun sequencing [9], DNA physical mapping [10], game theory [11], program synthesis [12], channel leak testing, codes, VLSI testing and AIDS screening and many others as in [13] and the references therein. Generally, in domains where queries can be answered by a non-human annotator, e.g.…”
Section: Introductionmentioning
confidence: 99%